Over again : a cognitive account of its meaning transference in the light of an image-schema based model - Do, Long Tuan (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article is the second in a two-article series that first critiques polysemic and monosemic theories to the meaning transference of over and then accounts for the word’s meaning transference from an image-schema based model. To be specific, this qualitative study aims to explain the processes of over’s meaning transference from spatial to non-spatial ones with 1350 instances in the 2017 Corpus of Contemporary American English, genre: Fiction. In the light of a combination of Multimodal Image Theory and Extended Conceptual Metaphor Theory, the mappings from SPACE domain to non-spatial domains, image-schema transformations, and a range of conceptual metaphors associated with over were systematically analysed to first identify the word’s senses and then account for the mechanisms of its meaning transference. It was found that mappings together with image-schema transformations are significant in motivating the meaning transference processes. The results of the study are summarized as follows: (i) The prototypical sense of over, represented by a pair of image complexes, designates the relative UP spatial positions and potential forces between the Trajectory (TR) and Landmark (LM) denoted by the preposition; (ii) its spatial senses cognitively generate within three spatial modalities of thought: Visual space, Maneuver space, and Kinetic space, and (iii) its non-spatial senses are attached to a range of conceptual metaphors which are spatially grounded. In other words, three spaces provide concrete image-schemas or experience which are virtually represented/ mapped on to abstract experience shown by the retaining salient TR-LM configurations.